2021
DOI: 10.1115/1.4050923
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics and Interfacial Surfactant Transport in Vascular Gas Embolism

Abstract: Vascular gas embolism - bubble entry into the blood circulation - is pervasive in medicine, including over 340,000 cardiac surgery patients in the US annually. The gas-liquid interface interacts directly with constituents in blood, including cells and proteins, and with the endothelial cells lining blood vessels to provoke a variety of undesired biological reactions. Surfactant therapy, a potential preventative approach, is based in fluid dynamics and transport mechanics. Herein we review literature relevant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Endothelial and pulmonary cellular injury and lung edema are the result of thromboinflammatory changes provoked by the release of damage-associated molecular patterns, normally not exposed to the innate immune system but recognized by the pattern recognition receptors when cell and tissue damage occur. Innate upstream systems like complement, toll-like receptors, and others induce downstream release (e.g., from the complement C5a-C5aR1 axis) of innumerable of inflammatory vasoactive mediators such as thromboxane, leukotrienes, cytokines, and coagulation factors with resultant increase in alveolocapillary permeability ( 1 , 3 , 12 , 30 , 35 37 , 79 , 80 ).…”
Section: Pathoanatomy and Importance Of Patient Positioningmentioning
confidence: 99%
See 4 more Smart Citations
“…Endothelial and pulmonary cellular injury and lung edema are the result of thromboinflammatory changes provoked by the release of damage-associated molecular patterns, normally not exposed to the innate immune system but recognized by the pattern recognition receptors when cell and tissue damage occur. Innate upstream systems like complement, toll-like receptors, and others induce downstream release (e.g., from the complement C5a-C5aR1 axis) of innumerable of inflammatory vasoactive mediators such as thromboxane, leukotrienes, cytokines, and coagulation factors with resultant increase in alveolocapillary permeability ( 1 , 3 , 12 , 30 , 35 37 , 79 , 80 ).…”
Section: Pathoanatomy and Importance Of Patient Positioningmentioning
confidence: 99%
“…It has also been shown that bubble volumes as small as 10 nL may persist for more than 35 minutes, which can significantly impede the delivery of oxygen to areas such as the brain and heart. It has been proposed that a diameter of 250 µm represents a threshold at which CBF is completely impaired ( 37 ). At these obstruction threshold values, variable reduction of CBF and cerebral function are likely and may explain the protean manifestations and the delayed response of HBOT ( 2 , 3 , 29 ).…”
Section: Pathophysiology: the Immunothrombotic And Endothelial Respon...mentioning
confidence: 99%
See 3 more Smart Citations